Media representations of national and international standardized testing in the Israeli education system. Issue 2 (4th March 2017) - Yemini, Miri; Gordon, Noa
ABSTRACT: This study applies discourse analysis to Israeli media coverage of national and international standardized examinations within Israel's public education system. Through systematic analysis of the topic in the two main Israeli financial publications between the years 2000 and 2013, we explore the nature and narrative of the media and compare the coverage of national and international standardized testing. We find that most of the media attention was devoted to international examinations, while national examinations were covered in a more limited yet critical way, perceived as unnecessary and even dubious. International examinations, in contrast, were described as axiomatic components of the education system. Articles on both national and international standardized testing criticize the education system, blaming teachers, the Ministry of Education, budget constraints, and marginalized populations for Israeli students' inadequate results. We frame our analysis by alignment of the articles along global–local and also neoliberal–humanistic axes. We structure our assessment within the global–local nexus and discuss the broader implications of the role of the testing in framing the local educational public discourse.